2019
DOI: 10.1038/s41467-019-13316-w
|View full text |Cite|
|
Sign up to set email alerts
|

Eliminating blood oncogenic exosomes into the small intestine with aptamer-functionalized nanoparticles

Abstract: There are disease-causing biohazards in the blood that cannot be treated with modern medicines. Here we show that an intelligently designed safe biomaterial can precisely identify, tow and dump a targeted biohazard from the blood into the small intestine. Positively charged mesoporous silica nanoparticles (MSNs) functionalized with EGFR-targeting aptamers (MSN-AP) specifically recognize and bind blood-borne negatively charged oncogenic exosomes (A-Exo), and tow A-Exo across hepatobiliary layers and Oddi’s sphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 40 publications
(56 reference statements)
1
67
0
Order By: Relevance
“…Nanoparticle-A-Exo conjugates can cross hepatobiliary layers and Oddi's sphincter into the small intestine, as validated by significant drop in circulatory A-exo, higher accumulation in the intestine and decreased lung metastasis in mice ( Fig. 5) [188].…”
Section: Exosomesmentioning
confidence: 89%
See 2 more Smart Citations
“…Nanoparticle-A-Exo conjugates can cross hepatobiliary layers and Oddi's sphincter into the small intestine, as validated by significant drop in circulatory A-exo, higher accumulation in the intestine and decreased lung metastasis in mice ( Fig. 5) [188].…”
Section: Exosomesmentioning
confidence: 89%
“…Importantly, cancer growth and in particular, metastatic expansion can be significantly reduced through targeting strategies to block and eliminate tumorderived exosomes [187,188] and/or aggressive CTCs [152,154] from the circulation of cancer patients, as discussed in the earlier sections. In the same way, cfDNA, apoptotic bodies, and exosomes can be used as noninvasive biomarkers for early detection of cancer cells as well as predicting therapy success/relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the strategy to suppress cancer metastasis via inhibiting the pro-metastatic functions of cancer-derived sEVs using antibodies against their surface proteins. In addition, an innovative design of aptamer-functionalized nanoparticles was shown to eliminate blood oncogenic sEVs into the small intestine, and attenuate oncogenic sEV-induced lung metastasis in mice [ 103 ]. This technology utilized positively charged mesoporous silica nanoparticles equipped with Epidermal Growth Factor Receptor (EGFR)-targeting aptamers specifically recognizing and binding the negatively charged oncogenic sEVs and towing them from blood to bile duct for elimination.…”
Section: Evs As Potential Therapeutic Targets In Cancermentioning
confidence: 99%
“…Clinical trials have shown that the human body can tolerate micromolar levels of oligonucleotides and deeper penetration of aptamers into the tumor core compared to antibodies [15] . Using positively charged nanoparticles that were functionalized with EGFR‐targeting aptamers, the Jia group reported a study to eliminate blood oncogenic exosomes into the small intestine [16] . As the first large‐scale application of aptamer technology for clinical diagnosis, Tan et al.…”
Section: Aptamer Technologymentioning
confidence: 99%